Critical Thinking Process Of Junior High School Students In Mathematical Problems Solving Based On Learning Styles - Andik Saputro; Ketut Budayasa; Endah Rahaju (International Journal of Trends in Mathematics Education Research, 2020)
The purpose of this study is to describe the critical thinking process of eighth grade junior high school students in solving mathematical problems in terms of visual, auditory, and kinesthetic learning styles. This type of research is a descriptive exploratory study with a qualitative approach. The subjects in this study were one female student with a visual learning style, one female student with an auditory learning style, and one student with a kinesthetic learning style. All three of these subjects have intermediate and equivalent mathematical abilities. Data collection is done by giving assignments and interviews conducted twice.The results obtained in this study are (1) The critical thinking process of eighth grade junior high school students with visual learning styles in solving mathematical problems, namely at the stage of understanding the problem, the subject does interpretation, analysis, evaluation, inference, and explanation. (2) The critical thinking process of eighth grade junior high school students with auditory learning styles in solving mathematical problems, namely at the stage of understanding the problem, the subject doing interpretation, analysis, inference, and explanation. (3) The critical thinking process of eighth grade junior high school students with kinesthetic learning styles in solving mathematical problems, namely at the stage of understanding the problem, the subject doing interpretation, analysis, evaluation, inference, and explanation. At the stage of preparing a plan for completion the subject conducts analysis, evaluation, inference, and explanation.